IMPACT OF AI ON ARCHITECTURE EDUCATION WITH RESPECT TO NEP 2020 - Gaurish Chandawarkar (IJRDO - Journal of Social Science and Humanities Research, 2025)
Artificial Intelligence implementation in India in architectural education is compliant with the national education policy (NEP) 2020 and is innovative, accurate, and sustainable in terms of design. IIT Roorkee, SPA Delhi, and CEPT University are among the leading institutions that have embraced AI in computational design, sustainability simulations and urban analytics. In spite of this, problems like inadequate infrastructure, faculty expertise and redesigning curriculums to name a few prevent mass adoption. This NEP 2020 opens up a possibility to incorporate the use of AI into the educational process in India allowing to shape the training program in which cross-disciplinary training will be undertaken, and sustainable actions maintained. To make AI maximize its potential in teaching architecture, the government, schools, and the private sector should collaborate. It should also aim at its adaptation to India culture or environment, ethical issues, and interaction with industry, among others. The effective application of AI will contribute to redesigning architectural education, which will become innovative, sustainable, and open.